PENGARUH KEPUASAN KERJA, BUDAYA KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS WAKAOKILI DESA KAONGKEONGKEA KECAMATAN PASARWAJO - Daholu, Ahmad; Suriadi, Suriadi; Zamlan, Nur (Jurnal Multidisipliner Kapalamada, 2024)
This study aims to determine the effect of job satisfaction, work culture, and work environment on employee performance at Wakaokili Public Health Center, Kaongkeongkea Village, Pasarwajo District. The research method used is multiple linear regression analysis. The population of this study consists of all employees of Wakaokili Public Health Center, totaling 35 people. A saturated sampling technique was applied, in which all members of the population were used as research samples. Data were collected through observation, interviews, question aires, and documentation. The results show that partially, job satisfac tion has a significant effect on employee performance, with a t-value of 2.733 & a significance level of 0.010. Work culture also has a significant effect on employee performance, with a t-value of 3.548 and a significan ce level of 0.001. In addition, the work environment has a significant effect on employee performance, with a t-value of 2.844 and a significa nce level of 0.008. Simultaneously, job satisfaction, work culture, and work environment have a significant effect on employee performance, as indicated by an F-value of 15.318 and a significance level of 0.000.